The Process of Decentralization Management Based on Foreign Experience (Economics and region, 2020)
The democratization of relations in society among developed countries, in most cases, is accompanied by the concept of fiscal decentralization. Today the priority in the world is the reform of public administration and decentralization which results in the abandonment of the centralized model of governance and the introduction of an effective system of territorial organization, financial self-sufficiency of local governments and expanding their budgets. In the current state of the economy of Ukraine and its regions there are a number of negative phenomena due to the loss of production potential, insufficient level of entrepreneurial activity, the presence of a significant level of shadow economy, resulting in economic instability and economic crisis. Thus, today there are many unresolved issues regarding the effective strategy of regulating the processes of decentralization of the management system, the equal distribution of powers at the local level and an effective strategy for the formation and distribution of the local budget. The task is to reform the country's inter-budgetary relations. However, the key to success in successfully reforming the state's governance system is to ensure economic decentralization with financial support from the central government in the initial stages. This strategy was followed by most developed countries in Europe and the world. Therefore, it is advisable to analyze the main advantages, risks and disadvantages of a decentralized management system based on foreign experience. Historical and modern strategies of reforming the management system of the leading countries of the world are considered.The scientific article considers the problematic aspects of the reforms and their specific implementation in countries such as Germany, Poland, Great Britain and Sweden. Prospects for the development of reform in Ukraine are identified and the main problems that arose at the first stage of the decentralization process are identified.
Keywords: decentralization; reform; management system; strategy; regional policy